Comparative analyses of responses to exogenous and endogenous antiherbivore elicitors enable a forward genetics approach to identify maize gene candidates mediating sensitivity to herbivore‐associated molecular patterns. (7th October 2021) - Poretsky, Elly; Ruiz, Miguel; Ahmadian, Nazanin; Steinbrenner, Adam D.; Dressano, Keini; Schmelz, Eric A.; Huffaker, Alisa
SUMMARY: Crop damage by herbivorous insects remains a significant contributor to annual yield reductions. Following attack, maize ( Zea mays ) responds to herbivore‐associated molecular patterns (HAMPs) and damage‐associated molecular patterns (DAMPs), activating dynamic direct and indirect antiherbivore defense responses. To define underlying signaling processes, comparative analyses between plant elicitor peptide (Pep) DAMPs and fatty acid–amino acid conjugate (FAC) HAMPs were conducted. RNA sequencing analysis of early transcriptional changes following Pep and FAC treatments revealed quantitative differences in the strength of response yet a high degree of qualitative similarity, providing evidence for shared signaling pathways. In further comparisons of FAC and Pep responses across diverse maize inbred lines, we identified Mo17 as part of a small subset of lines displaying selective FAC insensitivity. Genetic mapping for FAC sensitivity using the intermated B73 × Mo17 population identified a single locus on chromosome 4 associated with FAC sensitivity. Pursuit of multiple fine‐mapping approaches further narrowed the locus to 19 candidate genes. The top candidate gene identified, termed FAC SENSITIVITY ASSOCIATED ( ZmFACS ), encodes a leucine‐rich repeat receptor‐like kinase (LRR‐RLK) that belongs to the same family as a rice ( Oryza sativa ) receptor gene previously associated with the activation of induced responses to diverse Lepidoptera. Consistent with reduced sensitivity, ZmFACS expression was significantly lower in Mo17 as compared to B73. Transient heterologous expression of ZmFACS in Nicotiana benthamiana resulted in a significantly increased FAC‐elicited response. Together, our results provide useful resources for studying early elicitor‐induced antiherbivore responses in maize and approaches to discover gene candidates underlying HAMP sensitivity in grain crops. Significance Statement: Expression analyses and forward genetics approaches were used to identify a maize locus and receptor kinase gene candidate associated with response sensitivity to fatty acid–amino acid conjugate (FAC) elicitors widely present in insect oral secretions. Despite broad overlap, herbivore‐associated molecular pattern (HAMP) responses can be decoupled from damage‐associated molecular pattern (DAMP) responses, providing defined resources to investigate early signaling events underlying plant responses to diverse lepidoptera herbivores.